Report of the Expert Group on "Ground Water Management and Ownership" September 2007 - Planning Commission (Planning Commission, 2007)
The 2007 Expert Group Report on Ground Water Management and Ownership highlights the critical challenges of over-exploitation of India’s ground water resources, driven by agricultural subsidies, weak legal frameworks, and unsustainable extraction practices. With ground water supplying the majority of irrigation and drinking needs, the report underscores the need for urgent policy interventions, including legal reforms, community-based management, and artificial recharge measures. International comparisons with the U.S., Oman, Spain, and Mexico provide lessons on regulatory enforcement and cooperative management. Key recommendations emphasize revising ownership laws, promoting efficient water-use technologies, establishing local groundwater committees, and enhancing institutional coordination. The report concludes that sustainable ground water management is vital for agricultural productivity, environmental health, and long-term water security in India.
Planning Commission Yojana Bhawan New Delhi 110001
Planning Commission Yojana Bhawan New Delhi 110001
Keywords: Ground Water; Over-Exploitation; Sustainable Management; Legal Framework; Community-Based Management; Recharge Initiatives; Irrigation; Water Conservation; Policy Recommendations; Institutional Reforms